2020
DOI: 10.1021/acschemneuro.0c00558
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Eliglustat-Based Glucosylceramide Synthase Inhibitors as Substrate Reduction Therapy for Gaucher Disease Type 3

Abstract: There remain no approved therapies for rare but devastating neuronopathic glyocosphingolipid storage diseases, such as Sandhoff, Tay-Sachs, and Gaucher disease type 3. We previously reported initial optimization of the scaffold of eliglustat, an approved therapy for the peripheral symptoms of Gaucher disease type 1, to afford 2, which effected modest reductions in brain glucosylceramide (GlcCer) in normal mice at 60 mg/kg. The relatively poor pharmacokinetic properties and high Pgp-mediated efflux of 2 prompte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Previous studies in mice have suggested utility of brain permeant GCS inhibitor as treatment for neuronopathic GD but a clinical trial of miglustat (N-butyldeoxynojirimycin), an iminosugar, did not improve neurological end points in GD3 ( Schiffmann et al, 2008 ). Subsequently, more potent GCS inhibitors based on ceramide analogs have shown more promise in genetic nGD model and in chemically induced model ( Blumenreich et al, 2021 ; Cabrera-Salazar et al, 2012 ; Shayman, 2010 ; Wilson et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in mice have suggested utility of brain permeant GCS inhibitor as treatment for neuronopathic GD but a clinical trial of miglustat (N-butyldeoxynojirimycin), an iminosugar, did not improve neurological end points in GD3 ( Schiffmann et al, 2008 ). Subsequently, more potent GCS inhibitors based on ceramide analogs have shown more promise in genetic nGD model and in chemically induced model ( Blumenreich et al, 2021 ; Cabrera-Salazar et al, 2012 ; Shayman, 2010 ; Wilson et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is a relatively weak inhibitor of GCS with more potent inhibitory off-target effects ( Schiffmann et al, 2008 ). However, more specific and potent GCS inhibitors are showing early promise ( Schiffmann et al, 2020 ; Wilson et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is relatively weak inhibitor of GCS with more potent inhibitory off-target effects (Schiffmann et al, 2008). However, more specific and potent GCS inhibitors are showing early promise (Schiffmann, 2020; Wilson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is relatively weak inhibitor of GCS with more potent inhibitory off-target effects (Schiffmann et al, 2008). However, more specific and potent GCS inhibitors are showing early promise (Schiffmann, 2020;Wilson et al, 2020). (A) Quantitative analysis of total GluCer/GlcSph levels in Gba loxp/loxp Cx3cr1 Cre/wt mice and control mice (n=3 mice/group).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Indeed, these mutations can provoke the deposition of α-synuclein in the brain due to changes in the composition of sphingolipids [259]. Different glucosylceramide synthase inhibitors, a key enzyme in the first step of the glycosphingolipid synthesis, are being tested to palliate the visceral and blood symptoms of GD [260,261]. Moreover, new drugs with the ability to cross the BBB are currently being tested to reduce the levels of the glycosphingolipids in the brain of patients with PD [262].…”
Section: Cholesterol and Sphingolipidsmentioning
confidence: 99%